Comparative analysis of water quality models for the Cibarani Irrigation Channel using WASP and QUAL2Kw - Finna Fitriana; Doddi Yudianto; Yong Chan Seo (Sustinere: Journal of Environment and Sustainability)
Urban growth poses significant challenges to environmental quality, particularly through water pollution in river systems. This study investigates the water quality of the Cibarani Irrigation Channel, part of the Cikapundung River system in Bandung City, which is polluted by domestic wastewater and runoff. Rapid population growth and subsequent urban expansion have significantly deteriorated the water quality, affecting local communities that rely on the channel for fish farming and washing. Field tests showed that water quality failed to meet Class II standards, particularly for Dissolved Oxygen (DO), Ammonia (NH3), and Total Phosphorus (TP), as specified in Indonesian Government Regulation No. 22 of 2021. These findings emphasize the necessity for tools that can effectively support the development of pollution management strategies. This study compares the effectiveness of two water quality modeling tools, QUAL2Kw and WASP, in simulating water quality dynamics. The QUAL2Kw model demonstrated higher accuracy in predicting DO and NH3 concentrations, making it a more reliable tool for pollution control. Continuous model calibration is necessary to improve water resource management and mitigate pollution risks. The findings advocate for using QUAL2Kw in water pollution control strategies, highlighting its precision and its role in supporting sustainable environmental management policies.